Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

(1) For both \(Y=0.3, Z=0.7\) and \(Y=0.7, Z=0.3\) we have \(Y+Z=1\). Insufficient

(1) For both \(Y=0.3, Z=0.7\) or \(Y=0.3, Z=-0.7\) we have \(Y^2 < Z^2\). Insufficient

(1)+(2) From Statement (1) \(Z=1-Y\), and put in Statement (2): \(Y^2 < (1-Y)^2\) \(Y^2 < 1-2Y+Y^2\) \(2Y< 1\) \(Y<1/2\) Therefore, \(-Y>-1/2\) and \(1-Y>1-1/2\) and \(Z=1-Y>1/2\). Hence, \(Y<Z\). Sufficient

The correct answer is C.
_________________

I'm happy, if I make math for you slightly clearer And yes, I like kudos:)

Statement 1 : y+z = 1 , This can be possible in different cases : Case 1 : 0<y<1 and 0<z<1 Case 2 : y>=1 and as Z = 1 - y so z<=0 Case 3 : Z>=1 and as y = 1-z so y<=0 As we can't conclude whether y>z or y<z, statement 1 is not sufficient

Statement 2 : y^2 < z^2 , again which is possible in many cases case 1 : z>y>0 case 2 : z>0>y and z>|y| case 3 : y>0>z and y<|z| case 4 : 0>y>z As we can't conclude whether y>z or y<z, statement 2 is also not sufficient

By combining two statements and observing all the cases from both statements we can eliminate case 4 and case 3 from statement 2 as they violate the condition y + z = 1 from statement 1. So from the remaining cases which satisfy both statements we can clearly observe z>y . Hence we can say yes y<z.

(1) y + z = 1. The sum of two numbers is 1. Obviously from this info we cannot say which one is bigger. Not sufficient.

(2) y^2 < z^2 --> take the square root from both sides (we can safely do that since we know that both sides are non-negative): |y| < |z| --> z is farther from 0 than y is. Not sufficient.

(1)+(2) From (2): (y - z)(y + z) < 0. This implies that y - z and y + z have opposite signs. Since we know from (1) that y + z is positive, then y - z must be negative: y - z < 0 --> y < z. Sufficient.

1) y + z = 1: Scenario 1 - y= 0.3, z = 0.7, y + z = 1 and y < z; Scenario 2 - when y = 4, z = -3, y > z. Hence, not sufficient.

2) \(y^2\) < \(z^2\), From this statement, we can only that absolute value of y is greater than absolute value of z. y =-4 and z = 5, and \(y^2\) = 16 and \(z^2\) = 25, \(y^2\) < \(z^2\), but z > y. Not sufficient.

Consider both statements together. when both y and z are positive, y< z as \(y^2\) < \(z^2\). when only 1 of y and z are positive, y + z = 1 -> y = 1 -z . If y is negative, z has to be positive, so y < z when only 1 of y and z are positive, y + z = 1 -> y = 1 -z , if y is positive, z has to negative. If y = 4, z = -3. If y = 5, z = -4. If y=6, z=-5. As you can see |y| > |z|, but from statement 2, \(y^2\) < \(z^2\) or |y| < |z|. So, we can never have a scenario where y is positive and z is negative. Note that y and z both cannot be negative as y + z = 1.